Efeito do tratamento com toxina botulínica A na qualidade de vida de pacientes com bruxismo e dores orofaciais - Silva, Marcelo Caetano Parreira da (2020)
Introduction: Bruxism is defined as a parafunctional chewing activity, characterized by the clenching and / or grinding of teeth, which occurs both during sleep and during waking moments. Botulinum toxin type A presents itself as a therapeutic adjuvant to mitigate some symptoms caused by bruxism, due to the fact that it is a potent and specific myorelaxant, as it promotes the relaxation of the masticatory muscles. Method: Thirty female patients, aged between 18 and 40 years, who had bruxism and orofacial pain were selected. After careful anamnesis, the patients answered `a Visual Analogue Scale (VAS) to measure orofacial pain and another for quality of life. A randomization in two groups was performed: a control group (n = 15), where 0.05 ml of sterile saline solution were applied to the anterior bundle of the Temporal muscle and 0.2 ml to each masseter muscle; and an experimental group (n = 15), where 20 Units of Botulinum Toxin A (Botox®) were applied to each Masseter muscle and 05 Units to each Temporal muscle, in its most anterior bundle. All applications were performed on the same day by a previously calibrated operator. The patients returned for reevaluation after 30, 60, 90, 120, 150 and 180 days. In those times, patients. Results: In periods of 30, 60 and 90 days, a decrease in electromyographic activity was observed in the Botox group (p <0.001). When comparing pain and quality of life, a statistically significant difference was observed (p <0.001). Regarding quality of life, a significant difference was observed in the analyzed interval (p = 0.021). In the Botox group, considering the same evaluation interval regarding the comparison of pain and quality of life, there was a significant difference, respectively (p <0.001) and (p <0.001). When assessing the quality of life criterion between groups over time, a significant difference was observed in time 90 (p = 0.041), observing an improvement in quality of life in the Botox group. Conclusion: The application of intramuscular Botulinum Toxin type A in patients with bruxism and orofacial pain, proved to be an effective method, with regard to masseter muscle hyperactivity, in patients with bruxism, improving the quality of life of patients.